Minage de cryptomonnaies à Irkoutsk - Hugo Estecahandy (EchoGéo)
For several years, cryptocurrency mining has been developing on an industrial scale in Irkutsk Oblast in Eastern Siberia. This process of creating some digital currencies, including the bitcoin, requires significant computing power and therefore special resources. In addition to concentrating large quantities of these resources at an attractive price and a suitable climate, Irkutsk has certain socio-political characteristics that have facilitated the emergence of the activity. New dynamics are appearing in the region thanks to mining and, although still limited, are making the marginalized territory of Irkutsk emerge as a space suitable for certain digital activities.